Meritve temperaturnega polja na površini kontilitih slabov iz avstenitnega nerjavnega jekla - Kosmač, Alenka (Materiali in tehnologije, 2000)
Results and experimental procedure of the temperature field measurements on the surface of continuous casting (CC) austenitic stainless steels are described. The infrared linescanner Landscan LS113 was used for determination of the thermal strand state and temperature differences on the slab surface. The results obtained, confirmed the presence of hot spots on the surface, where cracks and surface depression aare the most frequent.
Keywords: nerjavna jekla; avstenitna jekla; kontinuirno ulivanje; temperaturno polje; meritve